Legal Protection for Teachers in Disciplinary Measures for Students in The Public Elementary School - Sapto Budoyo; Nadea Lathifah Nugraheni; Yefta Cristopher Susilo; Mahyuddin bin Arsat (Yayasan Keluarga Guru Mandiri, 2025)
Teachers in several regions have increasingly faced legal charges for administering disciplinary actions that were intended as educational corrections for students. This situation highlights the need for clear legal protection to safeguard teachers and other educational personnel as they perform their professional duties. The objective of this study is to examine the legal protections available to teachers and identify preventive measures to minimize disciplinary violations in public elementary school clusters in Clering. The study employs an empirical juridical methodology, combining secondary data as the theoretical foundation with primary data obtained from field observations, interviews, and community studies to evaluate the effectiveness of existing government regulations. The results indicate that legal protections for teachers in disciplinary cases are diverse and vary by jurisdiction, aiming to balance students' rights with the need to maintain order and discipline in schools. The study concludes that these protections promote fairness, prevent unjust criminalization of teachers, and strengthen professional autonomy. This research contributes to legal science by providing empirical evidence on how teacher protection policies operate in practice within Indonesia's educational context.